Assessment of the perioperative period in civilians injured in the Syrian Civil War - Hakimoglu,Sedat (2015)
BACKGROUND: wars and its challenges have historically afflicted humanity. In Syria, severe injuries occurred due to firearms and explosives used in the war between government forces and civilians for a period of over 2 years. MATERIALS AND METHODS: the study included 364 cases, who were admitted to Mustafa Kemal University Hospital, Medicine School (Hatay, Turkey), and underwent surgery. Survivors and non-survivors were compared regarding injury site, injury type and number of transfusions given. The mortality rate found in this study was also compared to those reported in other civil wars. RESULTS: the mean age was 29 (3-68) years. Major sites of injury included extremities (56.0%), head (20.1%), abdomen (16.2%), vascular structures (4.4%) and thorax (3.3%). Injury types included firearm injury (64.4%), blast injury (34.4%) and miscellaneous injuries (1.2%). Survival rate was 89.6% while mortality rate was 10.4%. A significant difference was observed between mortality rates in this study and those reported for the Bosnia and Lebanon civil wars; and the difference became extremely prominent when compared to mortality rates reported for Vietnam and Afghanistan civil wars. CONCLUSION: among injuries related to war, the highest rate of mortality was observed in head-neck, abdomen and vascular injuries. We believe that the higher mortality rate in the Syrian Civil War, compared to the Bosnia, Vietnam, Lebanon and Afghanistan wars, is due to seeing civilians as a direct target during war.